KNOWLEDGE MANAGEMENT ASSESSMENT IN EPC DIVISION PT. HUTAMA KARYA TO SUPPORT ACCELERATION AGILE TRANSFORMATION - Wicaksono, Widhi Ahmad; Hendarman, Achmad Fajar (Trunojoyo University of Madura, 2023)
The background of this research shows that the EPC Division at PT HUTAMA KARYA has relatively low performance when compared to other divisions in the company. One approach to overcome this performance problem is to apply the concept of Knowledge Management as a whole. By accelerating Agile transformation with the hope of having a positive impact on the performance of the EPC Division. This research uses mixed methods, combining surveys to all employees of the EPC Division of PT HUTAMA KARYA as well as conducting structured interviews with senior leadership representatives. A data triangulation approach was taken to integrate the analysis results from both sources, both quantitative and qualitative data. The results showed that the implementation of knowledge management in the EPC Division of PT HUTAMA KARYA is currently not optimal, so it needs development in several important aspects.